2002
DOI: 10.1530/eje.0.1470489
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up study of patients with adrenal incidentalomas

Abstract: Background: The incidence of adrenal incidentalomas has sharply increased in recent decades and concurrent subtle endocrine abnormalities, or even subclinical conditions, have been identified. Nonetheless, data concerning possible changes in adrenal size and/or hormonal pattern during follow-up are still inadequate. Objective: To evaluate long-term morphological and functional evolution of adrenal incidentalomas after initial diagnosis and to identify possible risk factors for hormonal hyperactivity and mass e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
146
3
11

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(179 citation statements)
references
References 20 publications
19
146
3
11
Order By: Relevance
“…To test the effectiveness of the different proposed cortisol cut-off after the 1-mg DST by using Bayesan analysis we had to define a priori the probability of autonomous cortisol secretion based on observed alterations in the tests used to assess the function of the HPA axis. We acknowledge that such a definition is arbitrary, but the presence of at least two alterations of the HPA axis has been widely used in previous work (14,22,23,24). Our data confirm that only a cut-point at 138 nmol/l achieves an incremental diagnostic effectiveness to detect functional adrenal autonomy.…”
Section: Discussionsupporting
confidence: 62%
“…To test the effectiveness of the different proposed cortisol cut-off after the 1-mg DST by using Bayesan analysis we had to define a priori the probability of autonomous cortisol secretion based on observed alterations in the tests used to assess the function of the HPA axis. We acknowledge that such a definition is arbitrary, but the presence of at least two alterations of the HPA axis has been widely used in previous work (14,22,23,24). Our data confirm that only a cut-point at 138 nmol/l achieves an incremental diagnostic effectiveness to detect functional adrenal autonomy.…”
Section: Discussionsupporting
confidence: 62%
“…Ohmori et al did not find a direct correlation between BMD, cortisol, and androgens; however, they suggested a possible role of DHEAS increase in counterbalancing the negative bone effects of endogenous hypercortisolism (33). Greater bone loss was also found in women on replacement therapy for 21-hydroxylase deficit and lower androgen levels (34), supporting the hypothesis on the importance of cortisol-to-androgen ratio in BMD maintenance (8,32,35). Finally, a strong correlation was observed between DHEAS and lumbar/femoral BMD values in healthy women (36).…”
Section: Discussionmentioning
confidence: 98%
“…Women with overt hypercortisolism had typical clinical symptoms of cortisol excess and more severe biochemical hypercortisolism; women with subclinical hypercortisolism had no typical symptoms of cortisol excess and milder biochemical abnormalities. Subclinical hypercortisolism is much more frequent in adrenal lesions than the overt one and the progression toward the overt form is very rare (34).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature changes in size have been reported in adrenal incidentalomas (Bastounis et al, 1997;Barry et al, 1998;Terzolo et al, 1998;Barzon et al, 1999;Siren et al, 2000;Libe et al, 2002;Grumbach et al, 2003), with such variations sometimes believed to reflect a more aggressive growth rate (Mansmann et al, 2004). Barzon et al (1999) reported that incidentalomas tend to undergo a period of increase in mass size but thereafter remain unchanged, suggesting the possible existence of a programmed end point of growth of adrenal masses.…”
Section: Discussionmentioning
confidence: 99%